PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPT SDN NO. 78 BALANG KABUPATEN TAKALAR - Ayuni, Dea; Rahmawati; Aeni Rahman, Syarifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using animated video learning media on the sciense learning outcomes of fourth-grade students at UPT SDN No. 78 Balang, Takalar Regency. This research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The population of this study consisted of all 43 fourth-grade students, and the entire population of this study consisted of all 43 fourth-grade students, and the entire population was used as the sample. Data collection techniques included learning outcome test (pre-test and post-test) and observation. The data were analyzed usinng descriptive statistical analysis and inferential statistical analysis through a paired sample t-test.The results showed that the mean pre-test score of students was 61,16, while the mean post-test score increased to 75, 93 after the implementation of animated video learnig media. This improvement indicates a change in students learning outcomes after the treatment was applied during the learning process. The t-test results revealed a t-value of -18,134 with a degree of freedom (df) of 42 and a significance value (sig. 2-tailed) of 0,001 <0,05. This indicates a significant difference between pre-test and post-test results.Therefore, it can be concluded that the use of animated video learning media has a possitive and significant effect on improving the science learnig outcomes of fourth-grade studentsat UPT SDN No. 78 Balang, Galesong Selatan District, Takalar Regency.